2016
DOI: 10.1111/jfs.12299
|View full text |Cite
|
Sign up to set email alerts
|

Phage‐Based Biosensor and Optimization of Surface Blocking Agents to Detect Salmonella Typhimurium on Romaine Lettuce

Abstract: The development of rapid detection technologies in parallel with understanding production practices will markedly improve the microbiological safety of leafy vegetables. The objective of this study was on the application of phage-based magnetoelastic (ME) biosensors and optimization of selected surface blocking agents for a rapid detection for Salmonella Typhimurium on Romaine lettuce. Initially, Romaine lettuce hearts surface was examined for structural differences followed by attachment and distribution of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Off-target binding of interferents can hinder biofunctionalization, obscure the transduction of specific interaction events, and decrease the signal-to-noise ratio (SNR) in the case of biosensors and generally compromise reproducibility, even when phage infectivity is not impacted. 51 For this reason, a common unit operation in phagefunctionalization is to follow conjugation with a blocking step, whereby the surface is flooded with an amphiphilic biological species (e.g., casein 78,168 or bovine serum albumin (BSA) 110,184 ), synthetic polymer (e.g., PEG 183,256 ), or aminepresenting molecule (e.g., ethanolamine 64,155 ) that will occupy nonfunctionalized sites on the surface without impeding the sensitivity of the functionalized sites. In this way, the nonspecific binding of proteins, and other components of the sample, is reduced, while specific reactions with the target analyte are (ideally) unaffected.…”
Section: Bacteriophage Layermentioning
confidence: 99%
“…Off-target binding of interferents can hinder biofunctionalization, obscure the transduction of specific interaction events, and decrease the signal-to-noise ratio (SNR) in the case of biosensors and generally compromise reproducibility, even when phage infectivity is not impacted. 51 For this reason, a common unit operation in phagefunctionalization is to follow conjugation with a blocking step, whereby the surface is flooded with an amphiphilic biological species (e.g., casein 78,168 or bovine serum albumin (BSA) 110,184 ), synthetic polymer (e.g., PEG 183,256 ), or aminepresenting molecule (e.g., ethanolamine 64,155 ) that will occupy nonfunctionalized sites on the surface without impeding the sensitivity of the functionalized sites. In this way, the nonspecific binding of proteins, and other components of the sample, is reduced, while specific reactions with the target analyte are (ideally) unaffected.…”
Section: Bacteriophage Layermentioning
confidence: 99%
“…Specifically for the detection of infectious agents, bacteriophages are recently regarded as alternative biorecognition element for biosensors due to their host bacteria specificity 33 34 35 . Replacement of antibodies with bacteriophages is very promising in order to reduce the cost and increase the stability even further 36 . Such a system will also allow for the detection and quantification of specific phages in the environment and from clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017 they confirmed that MRSA was detected specifically and selectively even in the presence of other competing bacteria [43]. Chen et al [44], and Mack et al [45] showed other exciting applications. Both papers describe the detection of Salmonella (S. enterica and S. typhimurium, respectively), at the surface of food products (chicken and lettuce, respectively).…”
Section: Bacteriophages Deposited On Solid Substratesmentioning
confidence: 95%